IMPLEMENTASI METODE TUTOR SEBAYA DALAM MENINGKATKAN MINAT DAN KREATIVITAS KOREOGRAFI SISWA KELAS XI MEKANIK OTOMOTIF 1 SMK NEGERI 1 AMPELGADING PEMALANG - Wahyuni, Eko (Jurnal Penelitian Pendidikan, 2014)
This research addresses the low interest and creativity of students in learning choreography. Studentsâ pre-test results shows that only 8 students out of 37 students managed to pass the minimum standard criteria. The purpose of this study is to determine and analyze the improvement in terms of interest and creativity by using Peer Tutors method.It is a method of learning together with the concept that there is a small group of mentors as the group guide. Peer tutoring method is a method of learning together with the concept of putting students in small groups. Students who areconsidered as faster learners in one group were appointed to become peer tutors for their peers. The activity triggers studentsâ interest and creativity either individually or in groups. This study uses the approach of classroom action research. The study was planned for two cycle. Each cycle consists of planning, implementation, observation and reflection. The research results shows that on the pre cycle there were only 8 out of 37 students (21,62 %) managed to pass the minimum score criteria of >75. On the first cycle there were 13 out of 37 students (35,13%) managed to pass the interest evaluation and 16 out of 37 students (43,24% ) passed the creativity evaluation. Finally, on the first cycle there were 18 out of 37 students (48,64%) managed to passthe interest evaluation and 31 out of 37 students (83,78%) passed the creativity evaluation. The improvement from the first cycle to the second cycle is 13, 51% for interest and 27.02 % for creativity.